2016
DOI: 10.18352/ijc.644
|View full text |Cite
|
Sign up to set email alerts
|

How innovation commons contribute to discovering and developing new technologies

Abstract: Abstract:In modern economics, the institutions surrounding the creation and development of new technologies are firms, markets and governments. We propose an alternative theory that locates the institutional origin of new technologies further back in the commons when self-organizing groups of technology enthusiasts develop effective governance rules to pool distributed information resources. The 'innovation commons' alleviates uncertainty around a nascent technology by pooling distributed information about use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Hess and Ostrom (2007:3) propose to look at "knowledge as a shared resource, a complex ecosystem that is a commonsa resource shared by a group of people that is subject to social dilemmas" and provide a rich oversight of contemporary research across many disciplines. Because we are concerned with economic issues, one relevant set of research about commons is the stream which considers the act of invention as a collective action problem (Allen 1983;Gächter et al 2010;Allen and Potts 2016). This literature addresses core issues of collective action, such as how to develop institutions to enable intangible common pool resources of information and knowledge.…”
Section: What Is the Problem Of Governance Of Science And Technology?mentioning
confidence: 99%
“…Hess and Ostrom (2007:3) propose to look at "knowledge as a shared resource, a complex ecosystem that is a commonsa resource shared by a group of people that is subject to social dilemmas" and provide a rich oversight of contemporary research across many disciplines. Because we are concerned with economic issues, one relevant set of research about commons is the stream which considers the act of invention as a collective action problem (Allen 1983;Gächter et al 2010;Allen and Potts 2016). This literature addresses core issues of collective action, such as how to develop institutions to enable intangible common pool resources of information and knowledge.…”
Section: What Is the Problem Of Governance Of Science And Technology?mentioning
confidence: 99%
“…Implementation, diffusion and acceptance within markets distinguishes innovation from pure invention [6]. Innovation success is therefore dependent upon both the technical advancement and the creation of markets, which requires active learning and creative entrepreneurial processes [7,8]. Freeman [9] shows that such activities produce waves of emergence and consolidation that can lead to network-building.…”
Section: Introductionmentioning
confidence: 99%
“…Within this networks, the scaling relationships (in addition to short-term transactions, institutional platforms that focus on building longer-term relationships are created) and scaling learning (realizing the longer-term opportunity to evolve institutional designs to accelerate learning among a growing number of participants) effects can be successfully established. Allen & Potts (2016) have proposed an alternative theory, which identifies the institutional origin of new technologies further back in commons when self-organizing groups of technology enthusiasts develop effective governance rules to pool distributed information resources. The study (Egbetokun, et al, 2017) has concluded by proposing that for innovation systems theory to remain relevant in the near future there has to be a shift from systems to networks, i.e.…”
Section: Review Of Institutional Aspect Of Innovative Developmentmentioning
confidence: 99%